Policy Perspectives on Educational Testing
X, 406 p.
Keywords: America faces a crisis in education and its accompanying effects on the nation's economic and social life. Educators and policy makers need to document the extent of this crisis, to gauge its potential impact, and to develop educational strategies that would boost achievement; this has turned the spotlight on educational assessment - the procedures, practices, and tools that educators use to measure the progress of students, both as individuals and groups. This book deals with a range of issues within the field of educational assessment, with an emphasis on those issues that have sparked the public policy debate in recent years. Much of this volume concerns itself with the impact of testing on various subgroups of the population - blacks, Hispanics, young children, and children considered to be of `below average' ability. Taken together, the contributions to this volume represent a broad range of views on differential test performance. (This book is part of the subseries of books based on the Ford Foundation's National Commission on Testing and Public Policy. Previous titles in this program include Gifford & Wing/Test in Defense, Gifford & O'Connor/Changing Assessments, Gifford/Test Policy and the Politics of Opportunity Allocation, and Gifford/Test Policy and Test Performance.).